Benefits of amplification for unaided speech discrimination in age-related hearing loss with flat type audiogram. Issue 1 (February 2023) - Ito, Akiko; Fukuda, Shigemi; Shimozawa, Maki; Abe, Kazuya; Kumada, Junko; Nakaya, Muneo
Abstract: Objective: The present study aimed to investigate whether hearing aid use can induce improvement as acclimatization effect in unaided speech perception in patients with age-related hearing loss. Methods: Fifty ears in 41 patients (age range: 65-91 years) diagnosed as age-related hearing loss were enrolled in this study. They used hearing aids for more than 8 hours per day. Unaided speech audiometry using 67-S Japanese monosyllabic word list was performed one or two years after the commencement of hearing aid use. The changes in the unaided speech discrimination score before and after the commencement of hearing aid use were analyzed. To investigate factors for improvement, the patients' backgrounds in terms of age, sex, pure tone average, unaided maximum speech discrimination score, fitting period (one year/two years), fitting ear (bilateral/unilateral), audiogram type (flat-type/other-type), and the level of amplification were also analyzed. Results: Significant improvement in the unaided speech discrimination score after hearing aid use was seen only in the flat-type audiogram group. More than half of older patients in the flat-type audiogram group improved their unaided maximum speech discrimination score 10 % or more. The analysis of aided hearing thresholds revealed that the flat-type audiogram group had significantly lower thresholds of 3kHz and 4kHz than the other-type audiogram group. The age, sex, pure tone average, fitting period, fitting ear, functional gain were not influential factors for improvement. On the other hand, unaided maximum speech discrimination score before using hearing aid and aided hearing threshold at 4kHz had a negative correlation with improvement. Conclusion: The findings suggested that older patients with age-related hearing loss whose audiogram is a flat type can benefit from amplification as means of improving their unaided speech perception since flat-type audiogram can be more easily adjusted to sufficiently amplify speech sound at high frequencies. It should be considered that the potential for experience-dependent plasticity is retained even in older adults.